The Influence of Principal’s Managerial Skills, Work Commitment, and Motivation on Teacher’s Organizational Citizenship Behavior (OCB) at Private Islamic Elementary School - Rachman, Muhammad Rizaly; Aslamiah, Aslamiah; Suriansyah, Ahmad (Journal of Elementary Educational Research, 2025)
Teachers are a key factor in educational success. Teacher quality is not only determined by formal performance, but also by their extra-role behavior called Organizational Citizenship Behavior (OCB). This study aims to analyze the influence of madrasah principals' managerial skills, work commitment, and work motivation on OCB of Private Elementary Madrasah (MIS) teachers in Banjarbaru City, both directly and indirectly through mediating variables. The study used a quantitative approach with a correlational design. The population included 214 teachers, with a sample of 139 respondents selected through proportional random sampling technique. Data analysis was performed using multiple linear regression and path analysis using the t-test and Sobel test. The results showed that madrasah principals' managerial skills significantly influenced OCB (β = 0.512; p = 0.047), work commitment (β = 0.513; p = 0.024), and work motivation (β = 0.432; p = 0.030). Work commitment also significantly influenced OCB (β = 0.608; p = 0.041), while work motivation had no direct effect (p = 0.085). However, the indirect effect of managerial skills on OCB through commitment and motivation was proven significant (p < 0.05). These findings emphasize the importance of strengthening the managerial skills of madrasah principals and increasing teacher commitment and motivation to encourage more optimal OCB.